Micropartículas de Spirulina sp. aplicadas em mistura para bebida de base láctea - Guarienti, Cíntia (2018)
Population aging requires new products development to meet consumer demand for nutritious, attractive, and healthy foods. Whey protein concentrate and Spirulina are promising ingredients for the food industry, as they present in their composition essential elements to nutrition and health beneficial. The microencapsulation technique may be an alternative to keep its functionality and allow greater control in the bioactive release. We aimed to develop a dairy-based drink for elderly segment, with microencapsulated Spirulina. The methodological steps consisted of Spirulina microencapsulation and microcapsules characterization; elaboration, physical-chemical and microbiological characterization of three formulations of milk-based beverage mixture (Control, with free Spirulina and with microencapsulated Spirulina); and evaluation of drink effects in vivo. Microencapsulation was performed through ionic gelation technique, in whic we evaluated encapsulation efficiency, water solubility, acid and basic media release profile, morphology, thermal resistance, chemical interactions and particle size of the microcapsules; besides the proximal composition and microbiological parameters of the mixture for the preparation of the beverage. Intervention in humans occurred with 40 individuals over 60 years of age, through daily consumption for 30 days. Biochemical markers of bone remodeling (acid phosphatase, alkaline phosphatase, calcium and creatinine) and lipid profile (total cholesterol, LDL, HDL and triglycerides) were evaluated before starting consumption and at the end of the intervention. Microcapsules have approximately 70% Spirulina, improved thermal stability and are resistant stomach acidity. With the microencapsulation industrial Spirulina application can be extended, however it is always necessary to evaluate food matrix interactions. Microalga bioactivity was altered by microencapsulation, and microencapsulated Spirulina formulation presented more promising results compared to in vivo study parameters. Results indicate that the microencapsulated spirulina milk-based beverage has potential to be introduced into the elderly diet.